A Unique Presentation of Metastatic Gallbladder Carcinoma. (16th December 2021) - Tian, Yuqian; Luu, Carrie; Carpenter, Danielle H.; Montenegro, Grace
Abstract : Gallbladder carcinoma can be challenging to diagnose and treat and usually leads to poor outcome, due to its aggressive nature and the nonspecific clinical presentation at early stage. We describe an interesting case of a 60-year-old female who presented with stage 3 appendiceal carcinoma after appendectomy was performed outside hospital. Further imaging workup demonstrated enlarged ovarian cysts and porcelain gallbladder. Upon exploration, she was found to have carcinomatosis and we proceeded with cytoreductive surgery (CRS) and hyperthermic intraperitoneal therapy (HIPEC). Final pathology demonstrated carcinoma from gallbladder primary.